Pesantren Dan Pengabdian Masyarakat (Studi Kasus Pondok Pesantren Dawar Boyolali) - Rustam Ibrahim (IAIN Ponorogo, 2016)
Abstract: When boarding schools are faced with community service, some of them are not willing to accept it. Survey of BPPM Maslakul Huda Islamic School, in collaboration with the P3M Jakarta concluded that three (25%) of the 12 pesantrens in Central Java do not receive community service. It is an irony, because pesantren was born and raised from the public. One of pesantrens that was born from community service is PP DawarBoyolali. PP Dawar proved that pesantren had a great contribution to the community. This study wanted to uncover the devotion PP Dawar to community, both in religious and economic empowerment, as well as the main reason of PP Dawar in performing community service. The method used in this study was a qualitative research method using case study design. Based on the research, it was found that PP Dawar was a community-based boarding school which had done community services by performing routine religious activities such as routine verses recitation, recitals of Qur’an for the orphans, and also serving the demand of societies that need Islamic teachers and religion teachers graduating from PP. DawarBoyolali. PP Dawar also helped the economy of the surrounding communities, by providing cheap labors, helping traditional broom and cracker home industry, and organizing donations to 500 orphans. The ideas or thoughts underlying PP Dawar’sdevotion are a sense of sincerity, an implementation on the religious science, a spirit of self-reliance, and a promotion for PP Dawar Boyolali itself. الملخص: عندما تُوجّه البسانترينات إلى وجود الخدمة الإجتماعية، كان بعضها لم يقبلها. دلّت الدراسة المسحية التي قام بها BPPM بسانترين